2017
DOI: 10.7554/elife.20937
|View full text |Cite
|
Sign up to set email alerts
|

Enforcement of developmental lineage specificity by transcription factor Oct1

Abstract: Embryonic stem cells co-express Oct4 and Oct1, a related protein with similar DNA-binding specificity. To study the role of Oct1 in ESC pluripotency and transcriptional control, we constructed germline and inducible-conditional Oct1-deficient ESC lines. ESCs lacking Oct1 show normal appearance, self-renewal and growth but manifest defects upon differentiation. They fail to form beating cardiomyocytes, generate neurons poorly, form small, poorly differentiated teratomas, and cannot generate chimeric mice. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…In a recent study, Shen et al. (2017) found that mammalian POU2F1/OCT1 and POU5F1/OCT4 occupy both overlapping and independent sets of target genes in ESCs and their daughters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Shen et al. (2017) found that mammalian POU2F1/OCT1 and POU5F1/OCT4 occupy both overlapping and independent sets of target genes in ESCs and their daughters.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) found that mammalian POU2F1/OCT1 and POU5F1/OCT4 occupy both overlapping and independent sets of target genes in ESCs and their daughters. Importantly, concomitant with the loss of OCT4 binding, OCT1 occupancy increased during differentiation ( Shen et al., 2017 ). This implies that POU/OCT factors may act in succession to regulate developmental processes based on sequential binding to common targets.…”
Section: Discussionmentioning
confidence: 99%
“…Although POU homeodomain proteins have been widely implicated in neuronal, immune cell, and stem cell development, the role of POU transcription factors during heart formation has remained elusive. In this regard, Oct4 has been implicated in mesoderm development, and a recent study found that Oct1 null ES cells failed to form beating cardiomyocytes upon directed differentiation (Li et al, ; Shen et al, ). However, aside from a single study examining the influence of mPou/Emb/Pou6f1 on cardiac alpha actinin gene expression, very little is known about the potential role of Pou6f1/ pouC during cardiac morphogenesis (Molinari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We compared this group of genes with Oct1 targets identified in T cells [18] and with Oct1/Oct4 targets identified in embryonic stem cells (ESCs, [46]. Oct4 levels are far higher than Oct1 in ESCs, resulting in most targets being occupied exclusively by Oct4, which has similar DNA binding specificity [46]. Of the 17 identified genes whose expression correlates with the tumor model, 8 were previously identified as direct Oct1 targets in T cells and 9 as Oct4 targets in ESCs ( Fig 5C).…”
Section: Genes That Are Differentially Expressed Between Chemical Andmentioning
confidence: 99%